PENGEMBANGAN E-COMIC BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN PADA MATERI KEBIJAKAN MONETER DAN KEBIJAKAN FISKAL KELAS XI SMA PARAMARTA 1 SEPUTIH BANYAK - Nurul Khotimah; Triani Ratnawuri (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Instructional media playing an important role in the communication process between teachers and students optimally established. However, it has not fully met the needs of students in the learning process. In the development of science and technology and the existence of the 4.0 industrial revolution, it increasingly encourages various offorts to take advantage of technology, this can encourage the implementation of learning to be more varied oan innovative. The purpose of this development is to produce an Android-based E-comic media as instructional media on monetary and fiscal policy instructional material of xi grade of Paramarta 1 Senior High School, which is valid and practical. This research was conducted using R&D (Research and Development) or development research with the 4D development model (Define, Design, Development, Disseminate). The process for developing E-comics begins with a validation stage by two media experts and one material experts. The e-comic was also tested in small groups to see the responses of Xl graders at Paramarta 1 Senior High School of Seputih Banyak. The results of the study show an increase, this is indicated by the results of the validation of the instructional media experts with a percentage of 91.2% with very strong criteria, the results of assessments by material experts with a rate of 91.4% with very strong criteria, and the results of online testing with small groups, ten from thirty students with a percentage of 88% included in the Very Strong standards. Based on the percentage obtained, e-comic is declared valid and practical to be used as instructional media.Keywords: Android, E-comics, Instructional Media, Technology